Implementation Protection Law Safety And Health Work (K3) on Worker Plantation Sector - Pramesti, Nadila Putri; Harun, Harun; Rizka, Rizka (Interest : Jurnal Ilmu Kesehatan, 2023)
Background: Worker plantation prone to to risk safety And health high work , however  implementation protection law Still become challenge . Limitations regulation , lack awareness And knowledge , capacity weak , as well lack of monitoring And enforcement law become factor main obstacle protection law for worker plantation . Study about implementation protection law safety and health work on worker plantation need done for evaluate challenge And existing problem as well as look for right solution for increase protection worker plantation. Aim of this study is to describe implementation protection law safety and health work (KS) on worker plantation sector.  Methods: A systematic review , with use article And book as source reference . Election source References done through machine Google search with criteria inclusion form article from journal national accredited Sinta And journal international Scopus accredited or non-Scopus issued No more from year 2020. Analysis done in a manner systematic with consider methodology research, findings main, and conclusion from every included research  in study.  Results: Implementation protection K3 law in plantations important For well-being worker . Required awareness , training, supervision, and enforcement firm law. Protection child laborer still minimal, necessary effort intensive . Expansion of the OSH program, increase of human resources, and repair system information required . Evaluation And repair sustainable important. The hope, effective implementation can upgrade condition work on the plantationour articles were found in this research article.  Conclusion: Implementation K3 law in the sector plantation important For guard safety worker. Needed awareness, training, supervision , and enforcement firm law . Protection child laborer Still need improved . Expansion of the OSH program, increase of human resources, and repair system information required . Evaluation And repair sustainable important. Expected condition work in the sector plantation can getting better with effective implementation.